Is it possible to prevent excessive synaptic pruning in schizophrenia? Possibilities and limitations - Pawlak, Agnieszka; Stefanowicz, Jakub; Kotkowska, Zofia; Gabryelska, Agata; Sochal, Marcin; Napieraj, Filip; Kotlicka-Antczak, Magdalena; Strzelecki, Dominik (Frontiers in Synaptic Neuroscience, 2025)
BackgroundSynaptic pruning is a critical neurodevelopmental process that eliminates redundant or weak synaptic connections to optimize brain circuitry. In schizophrenia, converging evidence from imaging, genetic, and postmortem studies suggests that this process is pathologically accelerated, particularly in the prefrontal cortex during adolescence. The resulting reduction in synaptic density has been implicated in disrupted neural connectivity observed in psychosis, with the onset of cognitive impairment and negative symptoms.ObjectiveThis review explores whether modulating aberrant synaptic pruning could serve as a preventive or early intervention strategy for schizophrenia. We analyze domains with emerging therapeutic relevance: tetracycline antibiotics, the complement system and C4 gene, kynurenine pathway modulation, epigenetic therapies, neuroprotective strategies (e.g., BDNF, NF-κB, progranulin), genetic and transcriptional regulators of pruning, and other new, mostly hypothetical, options. We also discuss the limitations of the impact on pruning.MethodsWe conducted a structured review of the mechanisms involved in pruning, as well as clinical trials, preclinical studies, and mechanistic models that investigate molecular targets influencing synaptic pruning in schizophrenia.ResultsSeveral molecular pathways have been implicated in abnormal synaptic pruning in schizophrenia, including complement C4A overexpression, kynurenine pathway imbalance (KYNA/QUIN), and dysregulation of microglial and transcriptional modulators such as MEF2C and TCF4. While retrospective studies suggest minocycline or doxycycline may reduce psychosis risk, randomized trials remain inconclusive. Emerging interventions, including LSD1 inhibitors, BDNF/progranulin enhancers, and lifestyle-based epigenetic modulation, show promise but require further validation in clinical settings. We also discuss the limitations of these methods, including safety considerations.ConclusionTargeted modulation of synaptic pruning represents a promising but complex therapeutic strategy. The timing, specificity, and reversibility of interventions are crucial to avoid disrupting essential neurodevelopment. Future efforts should focus on identifying biomarkers for patient stratification and validating preventive strategies in high-risk populations.